Uso de diluyentes para la conservación de semen equino en Colombia (2023)
Thanks to the need to increase the business of equine breeding in Colombia, biotechnology centers have found it necessary to implement the use of diluents as a measure for long-term seminal conservation, in such a way that the stress caused to the cell during the cooling of semen can be reduced. Said diluents are composed of different substances, which thanks to their properties allow the maintenance of the motility, vitality, and morphology of the sperm until the moment of artificial insemination.